Nilai-Nilai Kepahlawanan Kisah Kresnayana dan Ramayana sebagai Sumber Pendidikan Karakter pada Mata Pelajaran IPS - Zulaikha Tri Astuti; Winda Nurul Annisa (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
Indonesia faces numerous social problems, which stemming from the same root: character. Therefore, character education was crucial to instill in the next generation. One of the values of character education that can be transmitted to students is the value of heroism and it can be instilled through integration with social studies subjects. Through it, understanding the values of heroism can be presented through learning resources which found in society, such as the stories of Kresnayana and Ramayana. This study aims to examine the values of heroic character contained in the Kresnayana and Ramayana narratives and compare it with the current growing values. This research using literature study as method. The data sources used include interpretations of reliefs, kakawin, and stories that narrate the story of Kresnyana and Ramayana. The heroism character values presented by these two narratives includes courage in facing challenges, courage in defending truth and justice, love of the homeland, willingness to sacrifice, and patriotism. Due to the long gap between the creation of the Kresnayana-Ramayana narrative and the birth of ideas about Human Rights, various adjustments were required both in the presentation of the core message and in the medium for presenting it as a learning resource.